Design Automation for Differential MOS Current-Mode Logic Circuits - Badel, Stéphane; Baltaci, Can; Cevrero, Alessandro; Leblebici, Yusuf (Springer International Publishing : Imprint: Springer, 2019)
This book discusses the implementation of digital circuits by using MCML gates. Although digital circuit implementation is possible with other elements, such as CMOS gates, MCML implementations can provide superior performance in certain applications. This book provides a complete automation methodology for the implementation of digital circuits in MCML and provides an extensive explanation on the technical details of design of MCML. A systematic methodology is presented to build efficient MCML standard-cell libraries, and a complete top-down design flow is shown to implement complex systems using such building blocks.